Development of male sterile broccoli lines with raphanus sativus cytoplasm and assessment of their value for breeding purposes - Kamiński Piotr (Journal of Horticultural Research, 2013)
The aim of this study was to obtain new broccoli lines with cytoplasmic male sterility trait for the development of the modern F1 hybrids. CDT70 cauliflower line obtained in the Research Institute of Horticulture, formerly Research Institute of Vegetable Crops, Skierniewice, Poland, with the reliable cytoplasmic male sterility from Raphanus sativus (Ogu-INRA) was selected as a source of this trait. Three broccoli lines: BMi, BCr1 and BCr2 were used as donors of commercial characters in all cross combinations with sterile components. Selected fertile broccoli genotypes were characterized by good quality, uniformity and high level of self-compatibility. The breeding procedure included three consecutive back crosses of male sterile genotypes with fertile broccoli lines that lasted from 2008 to 2012. In each generation, self-compatibility level, the stability of the male sterility trait and ability for the generative propagation of back-crossed genotypes were tested in comparison with donor broccoli lines in the greenhouse. The agronomical and morphological characters of the back-crossed progeny were also evaluated in the field. As a result, three CMS broccoli lines of Bc3 generation with good quality and high seeding index, suitable for the breeding purposes, were obtained.